Seismic Vulnerability Assesment of Plaza Bogor Building in Bogor City - Lutfi, Muhamad; Chayati, Nurul; Muliyana, Indra; Insan, Muhammad Khaerul (Universitas Ibn Khaldun Bogor, 2026)
Plaza Bogor Building is a commercial building that is the center of economic activity that has been established for 28 years, it is important to conduct a structural vulnerability analysis to ensure the strength of the building structure is able to withstand potential earthquakes that can occur again at any time. This study aims to assess the level of vulnerability of the Plaza Bogor Building structure to earthquakes using the Rapid Visual Screening (RVS) method based on FEMA P-154 2015 and testing the quality of concrete using the Hammer Test method, and structural analysis using ETABS v.21 software to evaluate the performance of the Plaza Bogor Building structure against earthquake loads based on performance-based methods. The analysis results show that the final RVS value of the Plaza Bogor Building does not experience damage of 99,874% against earthquakes. All structural elements of the columns, beams, and slabs of the Plaza Bogor Building that have been tested with the Hammer Test get the value of concrete quality on the basement floor column to the fourth floor in the range of 41,55MPa – 57,10MPa, the value of concrete quality on the first floor beam to the fourth floor in the range of 41,61MPa – 51,98MPa, and the value of concrete quality on the first floor slab to the fourth floor in the range of 51,57MPa – 57,10MPa where the value meets the fc' >21MPa standard based on SNI 2847:2019. The results of the analysis of the upper structure of the Plaza Bogor Building against static earthquake loads and dynamic earthquake loads in the ETABS program show that there are eleven out of 906 beams that experience overstress and there are two out of 511 columns that experience overstress, so the safety of structural elements in the Plaza Bogor Building is 99,08% against earthquakes.